Rich in Fiber Biscuits Formulation with Katuk Leaf Flour Fortification (Sauropus androgynus) and Roasting Time Variation - Irmayanti Irmayanti; Rita Sunartaty; Chairil Anwar (Serambi Journal of Agricultural Technology, 2019)
Biscuits are usually made with flour, the biscuit's water content is not less than 5%. Usually the biscuit formulation is made by adding additional ingredients such as fat, sugar or salt as well as developing ingredients. Then also additional ingredients such as chocolate, fruits and spices that have an influence on taste. Katuk leaves contain 7% protein and up to 19% crude fiber. This leaf also contains vitamin K, pro-vitamin A (beta-carotene), B and C. Because the fiber content in katuk leaves is still high, katuk leaves can still be used as a new food source, reprocessed into biscuits. The purpose of this study was to determine the effect of katuk leaf flour substitution and roasting time on the quality of biscuits. The research used factorial completely randomized design (RAL) with the addition factor of katuk leaf flour 2,3 and 4% and roasting time was 20.25 and 30 minutes. The best treatment in this study was biscuits with the addition of katuk leaf flour 4% and roasting time for 30 minutes with a water content of 11.66%, ash content of 1.18%, fiber content of 0.60%, organoleptic value of 4.38 (very likes) taste organoleptic value 4.20 (very like), and texture organoleptic value 4.35 (very like). Keywords :